2021
DOI: 10.1134/s1070363221110128
|View full text |Cite
|
Sign up to set email alerts
|

A New Series of 1,3,4-Oxadiazole Linked Quinolinyl-Pyrazole/Isoxazole Derivatives: Synthesis and Biological Activity Evaluation

Abstract: A series of 1,3,4-oxadiazole bridged pyrazole/isoxazole bearing quinoline derivatives has been designed and synthesized by a clean and convenient method. Structures of the newly synthesized compounds have been confirmed by FTIR, 1 H and 13 C NMR, and HRMS spectral data. The titled compounds have been evaluated for their molecular docking guided antimicrobial and anti-inflammatory activity. One of 1,3,4-oxadiazole bridged quinolinyl-pyrazole derivatives has interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…[29] Inhibition of dihydrofolate reductase (DHFR) leads to inhibit folate metabolism which can cause bacterial death. [30] The docking study of similar types of compounds was reported with dihydrofolate reductase (DHFR) [31] and DNA gyrase [32] As compound 4 n was found to be most potent from the invitro antibacterial screening, we studied the possible binding of 4 n with PDB IDs 1KZN and 2W9H. A closer visual inspection of a binding pose of the ligand with protein is depicted in Figures 3A and 3B.…”
Section: Molecular Docking Studymentioning
confidence: 96%
“…[29] Inhibition of dihydrofolate reductase (DHFR) leads to inhibit folate metabolism which can cause bacterial death. [30] The docking study of similar types of compounds was reported with dihydrofolate reductase (DHFR) [31] and DNA gyrase [32] As compound 4 n was found to be most potent from the invitro antibacterial screening, we studied the possible binding of 4 n with PDB IDs 1KZN and 2W9H. A closer visual inspection of a binding pose of the ligand with protein is depicted in Figures 3A and 3B.…”
Section: Molecular Docking Studymentioning
confidence: 96%
“…The direct cyclisation of methyl nicotinoyl hydrazone to 1,3,4-heterocyclic compounds were completed by using various reagents such as acetic anhydride, phosphorus penta oxide, thionyl chloride, and polyphosphoric acid. Increasing bacterial resistance against antibiotics, leading to many drugs interaction and reducing the drug efficacy, such as local tissue irritation, narrow antimicrobial spectrum and Interference with wound healing processes (9,10) . For this reason, there is always a need to develop new types of synthetic agents and reduce the toxic effect by modifying the chemical structure.…”
Section: Introductionmentioning
confidence: 99%